2020
DOI: 10.3126/ijasbt.v8i1.28252
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Plasmid Profile of Resistant Klebsiella pneumoniae Isolates in Patients with Urinary Tract Infection in Nasarawa State, Nigeria

Abstract: Klebsiella pneumoniae has been identified as an urgent threat to human health based on its increasing antimicrobial resistance to the beta-lactamases and Carbapenemases. The pathogen has become a threat to both patients and healthcare providers as its incidence is on the increase, becoming a major global healthcare issue. The study was aimed at characterizing and determining the plasmid profile of resistant Klebsiella pneumoniae isolates from urinary tract of patients at Dalhatu Araf Specialist Hospital Lafia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Accordingly, research by Dong et al found that each isolate included five plasmids, and each measuring 178,177.5, 99.7, 11.9, and 5.6 kb in size (Dong et al, 2018). Another study from the Neonatal intensive care unit of an Indian hospital reported that the 66 kb, 38 kb, and 6 kb plasmid sizes were identified in carbapenem-resistant K. pneumoniae clinical isolates (Orole and Hadi, 2020). The presence of many plasmids in these isolates may serve as a potential source for the spread of highly resistant genes to other bacteria and humans, which poses a risk to the commonly used antibiotics to treat infections.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, research by Dong et al found that each isolate included five plasmids, and each measuring 178,177.5, 99.7, 11.9, and 5.6 kb in size (Dong et al, 2018). Another study from the Neonatal intensive care unit of an Indian hospital reported that the 66 kb, 38 kb, and 6 kb plasmid sizes were identified in carbapenem-resistant K. pneumoniae clinical isolates (Orole and Hadi, 2020). The presence of many plasmids in these isolates may serve as a potential source for the spread of highly resistant genes to other bacteria and humans, which poses a risk to the commonly used antibiotics to treat infections.…”
Section: Discussionmentioning
confidence: 99%